PEMELIHARAAN IKAN KOI (CYPRINUS CARPIO) PADA KOLAM BETON - MAS’UD, NURYADIN IBNU; AFFANDI, RANGGA IDRIS (GANEC SWARA, 2024)
Koi (Cyprinus carpio) is a type of fish that belongs to a strain of common carp (Cyprinus carpio). Koi fans in Indonesia not only keep koi fish in ponds, but also take part in koi contests so that they can increase the prestige of their owners. Koi fish is a freshwater ornamental fish commodity that has economic potential in national and international markets. This research aims to determine the performance of koi fish cultivation in concrete ponds. This research activity was carried out in January-February 2024 at the Lingsar Fish Seed Center (BBI), West Lombok, West Nusa Tenggara. The data collection techniques used in this research are descriptive methods and field observations. The results obtained are koi fish cultivation activities including pond preparation, selection and distribution of seeds, the grow-out process where the grow-out process includes feed management, water quality management and koi fish health management. Next, growth observations were carried out where growth for 21 days could provide significant results, which can be seen from the absolute weight and length obtained, namely 2.3 grams and a length of 3.28 cm. Then the FCR value obtained was 0.53 and SR 99.6%. Meanwhile, for optimal maintenance water quality, the maintenance temperature range is around 26-30°C and the pH is around 6.5-8.0. From these data it can be said that the koi fish cultivation has been successful